Pengendalian Kualitas Menggunakan Metode Statistical Quality Control (SQC) pada Kain Teteron Rayon di PT. ABC - Batista, Syifa Dida; Hendrawan, Aloysius Tommy; Khoiri, Halwa Annisa (Fakultas Teknik Universitas Tulang Bawang, 2026)
Abstract PT ABC is one of the companies in the textile industry (clothing) with dyeing, printing, and finishing units located in the Karanganyar area. This study aims to analyze quality control in the Teteron Rayon fabric dyeing production process at PT. ABC using the Statistical Quality Control (SQC) method. This method involves several statistical tools, namely histograms, Pareto diagrams, P-Chart analysis, and fishbone diagrams. Based on the results of the histogram analysis of defect data over a 12-month period, it was found that the highest defect rate occurred in March 2025 at 20,776 yards. The results of the Pareto analysis showed that the most dominant type of defect was streaks, with a total of 36,602 yards or 19% of the total defects. The p-chart analysis revealed that most of the production results were outside the control limits, with only one production period (February 2025) being within the statistical control limits. Meanwhile, fishbone analysis shows that the main causes of striped defects include lack of operator training, low understanding of grey fabric quality, suboptimal machine maintenance, work methods that do not comply with SOP, and weak supervision of the production process. With this, the company is advised to improve workforce training, improve maintenance systems, and tighten operational supervision to reduce the number of defects and improve product quality. Keywords: Defect Dyeing, Fishbone, Kain Teteron Rayon, P-Chart, Pareto Diagram Statistical Quality Control.